Rattan (Calamoideae) Diversity and Biomass Change in Different Habitat Types During Two Years - Nadine Ruppert,; Asyraf Mansor,; Shahrul Anuar Mohd Sah, (Tropical Life Sciences Research, 2017)
Rattans (subfamily Calamoideae) are an important component of the forests of the Old World. However, few studies have been conducted on the distribution of these abundant palms within different habitats, specifically in Peninsular Malaysia. This study was aimed at assessing rattan diversity, abundance and biomass change across two different habitat types, namely, dipterocarp forests and fresh-water swamps within the Segari Melintang Forest Reserve, Perak, within two years. All rattan stems within five 100 m × 100 m sized study plots (A–E) of the two habitat types were counted in 2011 and 2013, and Shannon-Wiener diversity indices (H’) and Bray-Curtis dissimilarity indices were calculated. A total of 11 species from 5 genera (161 stems ha–1) were sampled. Rattan abundance was higher in all swamp plots; however, rattan diversity (H’) was highest in the dipterocarp plot (D: H’(2011)1.79; H’(2013)1.84). Bray-Curtis indices of rattan abundance (highest similarity in swamp: plot BC(2011) 0.484, BC(2013) 0.262) and biomass were highest for study plots with the same vegetation types in both years. For rattan biomass, the most similar plot pairs changed during the years: dipterocarp plots A and D were most similar in 2011 (0.509), and swamp plots B and C were most similar in 2013 (0.282). This study helped contribute information regarding the distribution and dynamics of rattans in a primary rainforest of Peninsular Malaysia. Rotan (subfamily Calamoideae) adalah satu komponen penting dalam hutan paleotropik. Walau bagaimanapun, tidak banyak kajian yang dijalankan berkaitan kelimpahan palma ini, khususnya di Semenanjung Malaysia. Kajian ini bertujuan untuk menilai kepelbagaian rotan, kelimpahan, dan biomassa rotan di dua jenis habitat yang berbeza, iaitu hutan dipterokarpa dan paya air tawar di dalam Hutan Simpan Segari Melintang, Perak selama tempoh dua tahun. Semua batang rotan dalam lima plot kajian (A–E) berukuran 100 × 100 m setiap satu di kedua-dua jenis habitat telah dikira pada tahun 2011 dan 2013 dan indeks kepelbagaian Shannon-Wiener (H') dan indeks ketidak samaan Bray-Curtis turut dikira. Sebanyak 11 spesies dari 5 genera (161 batang ha–1) telah disampel. Kelimpahan rotan adalah lebih tinggi di plot kawasan berpaya, bagaimanapun, kepelbagaian rotan (H') adalah paling tinggi dalam kawasan dipterokarpa plot D: H'(2011)1.79; H'(2013)1.84. Indeks-indeks Bray-Curtis bagi kelimpahan (persamaan tertinggi di paya air tawar: plot-plot BC(2011) 0.484, BC(2013) 0.262) dan biomassa adalah tertinggi bagi plot kajian dengan jenis tumbuh-tumbuhan yang sama untuk kedua-dua tahun. Bagi biomassa rotan, pasangan plot paling serupa berubah dari tahun ke tahun: plot-plot dipterokarpa A dan D adalah paling serupa bagi tahun 2011 (0.509), plot-plot berpaya B dan C adalah paling serupa bagi tahun 2013 (0.282). Kajian ini dapat membantu dalam menyumbang maklumat kepada taburan spesies rotan tempatan di hutan hujan primer Semenanjung Malaysia.